How do you multiply #2(a^2 + a)(3a^2 + 6a)#?

1 Answer
Apr 27, 2017

Answer:

#6a^4+18a^3+12a^2#

Explanation:

First, apply the distributive property to get:
#(2a^2+2a)(3a^2+6a)#

Here, you can use FOIL to get all the terms.
F irst --> #2a^2\cdot 3a^2=6a^4#
O uter --> #2a^2\cdot 6a=12a^3#
I nner --> #2a\cdot 3a^2=6a^3#
L ast --> #2a\cdot 6a=12a^2#

You then have #6a^4+12a^3+6a^3+12a^2=6a^4+18a^3+12a^2#

You can also apply FOIL first and then multiply everything by 2.
#2(3a^4+6a^3+3a^3+6a^2)#
#=2(3a^4+9a^3+6a^2)#
#=6a^4+18a^3+12a^2#